Enzymatic in situ saccharification of chestnut shell with high ionic liquid-tolerant cellulases from Galactomyces sp. CCZU11-1 in a biocompatible ionic liquid-cellulase media. (February 2016) - He, Yu-Cai; Liu, Feng; Gong, Lei; Di, Jun-Hua; Ding, Yun; Ma, Cui-Luan; Zhang, Dan-Ping; Tao, Zhi-Cheng; Wang, Cheng; Yang, Bin
Graphical abstract: Highlights: Galactomyces sp. CCZU11-1 could produce high IL-tolerant cellulase. The optimum concentration of IL [Mmim][DMP] in the culture media was 5% (w/v). Galactomyces sp. CCZU11-1 could effectively remove xylan. High xylanase activity was obtained using untreated chestnut shell as carbon source. Effective enzymatic hydrolysis was shown in the IL [Mmim][DMP] (20%, w/v) media. Abstract: In this study, it was the first time to report that the cellulases of Galactomyces sp. CCZU11-1 showed high activity and stability in the culture and reaction media containing IL [Mmim]DMP. Using untreated chestnut shell (CNS) as carbon source in the culture media containing IL [Mmim]DMP (5%, w/v), high activity of FPA (28.6 U/mL), xylanase (186.2 U/mL), and CMCase (107.3 U/mL) were obtained, and 184.9 mg/L of total protein was achieved. Furthermore, the changes in the structural features (crystallinity, morphology, and porosity) of the solid residue of CNS utilized with Galactomyces sp. CCZU11-1 were characterized with Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray diffraction. After was enzymatically hydrolyzed with the prepared crude enzymes in IL diluted to 20% (w/v), a high yield of reducing sugars, 62.1%, was obtained. Significantly, Galactomyces sp. CCZU11-1 showed high potential for the efficient transformation of lignocellulosic materials to glucose in a single-step process.